INVESTMENT PARTNERSHIP BETWEEN THE STATE AND BUSINESS ON THE TRANSPORT: PATH AND PROBLEMS - Kudrytska, N. V. (Science and Transport Progress, 2008)
In the article the basic forms of state-private partnership as important instrument of upgrading the quality and competitiveness of transportation services in the world and European transport markets and inviting the investments in development of the transport-and-road complex ofUkraineare considered.